Retroperitoneal Urinoma Spontaneously Drained in the Scrotum Repaired with Gracilis Muscle Flap: A Case Report - Emanuela Altobelli; Alfredo Maria Bove; Federico Sergi; Maurizio Buscarini (Case Reports in Urology)
Aim. To report a unique case of retroperitoneal urinoma extending to the scrotum through the spermatic cord and successfully treated with nephrostomy, drainage, and gracilis muscle flap.